2018
DOI: 10.1364/boe.9.001852
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of seborrheic keratosis from basal cell carcinoma, nevi and melanoma by RGB autofluorescence imaging

Abstract: A clinical trial on the autofluorescence imaging of skin lesions comprising 16 dermatologically confirmed pigmented nevi, 15 seborrheic keratosis, 2 dysplastic nevi, histologically confirmed 17 basal cell carcinomas and 1 melanoma was performed. The autofluorescence spatial properties of the skin lesions were acquired by smartphone RGB camera under 405 nm LED excitation. The diagnostic criterion is based on the calculation of the mean autofluorescence intensity of the examined lesion in the spectral range of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…For some patients, keratinized squamous epithelium was found to cause autofluorescence increase, as opposed to the expected signal decrease in the examined lesion. Actually, it is possible to discriminate seborrheic keratosis from BCC and nevi with sensitivity and specificity close to 100%, based on autofluorescence intensity increase in G spectral channel [23]. In our present study, skin hyperkeratosis was diagnosed for patient no.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…For some patients, keratinized squamous epithelium was found to cause autofluorescence increase, as opposed to the expected signal decrease in the examined lesion. Actually, it is possible to discriminate seborrheic keratosis from BCC and nevi with sensitivity and specificity close to 100%, based on autofluorescence intensity increase in G spectral channel [23]. In our present study, skin hyperkeratosis was diagnosed for patient no.…”
Section: Discussionmentioning
confidence: 51%
“…Dermoscopic criteria for skin cancer detection in situ, such as increased vascularity, the presence of pigmentation, ulceration, inflammation and keratinization are related to the appearance of unique autofluorescence features of biological tissue . The method of autofluorescence has already been shown to improve the identification of primary BCC and SCC lesions that may not be visible to the naked eye or dermoscopy . Considering the criteria for non‐melanoma skin cancer identification, healthy skin has intense green autofluorescence whereas cancerous areas may appear darker .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that sensitivity and specificity of skin lesion diagnostics by smartphone‐detected auto‐fluorescence images can be very high . There are several differences between our DRS work and the auto‐fluorescence method.…”
Section: Resultsmentioning
confidence: 94%
“…There are two types of skin tumours, non-melanoma skin cancer (NMSC) and malignant melanomas (MM). As compared to NMSC, MM has a more aggressive modality with an estimated mortality of 85% for all fatal skin cancers 1 . The most common NMSCs include basal cell carcinoma (BCC), which constitutes approximately 80% of new cases, and squamous cell carcinoma (SCC), which constitutes approximately 20% of new cases 1 .…”
Section: V1mentioning
confidence: 99%